The orientation of microbiological processes in the dark-gray podzolic soil with different technologies of growing of soybean - Малиновська, І.М. (Problems of Environmental Biotechnology, 2012)
We investigated the orientation and intensity of microbiological processes in the dark-gray podzolic soil with using different fertilization systems and technology of soybean production. Was found, that technology of plowing of crop by-products and introduction N40P60K60 is the best among the studied variants. It enables to create in the root zone of soybeans stable microbial community, substantially reduce the number of physiological and biochemical activity of denitrifying bacteria, reduce the activity of the mineralization of humus at the 2.43 times. In terms of agro-chemical yield of soybean significantly (r = 0,666-0,999) positively correlated with the number of nitrifiers, pedotrofov, the total number of microorganisms in the soil nitrogen content of all shapes and potassium is negatively correlated with the number of Azotobacter, physiological and biochemical activity pedotrofov, oligotrophicity coefficients, mineralization of nitrogen and humus.